Optimal dispatch of LTC and switched shunt capacitors in smart grid with plug-in electric vehicles - Deilami, Sara; Masoum, Mohammad (IEEE, 2013)
Smart grids will facilitate transformation from the centralized, producer-controlled network to a less centralized and more consumer-interactive system while promoting distributed renewable energy resources, plug-in electric vehicles (PEVs) and smart appliances. It is well-known that random (uncoordinated) charging of PEV batteries can have detrimental impacts on voltage profiles and grid losses particularly during the peak load hours. This paper investigates the possibility of preventing or mitigating these issues by considering PEV charging activities in the optimal dispatch of LTC and switched shunt capacitors (SSCs). To do this, forecasted daily load curves of residential feeders with PEV charging are incorporated in the optimal LTC and SSC scheduling. Simulation results without and with optimal dispatch are presented for (un)coordinated charging of PEVs considering harmonic distortions due to the presence of nonlinear loads.